Front view of the airport terminal building - National Library of Jamaica (National Library of Jamaica, 1960)
Image showing control centre at the Palisadoes airport .
Keywords: National Library of Jamaica -- Photograph -- Jamaica; Airports - Kingston Palisadoes -- Photographs -- Jamaica